The Effect of Corporate Governance on Earnings Management: Evidence from FTSE350 Companies. - Luo, Fan (2020)
This paper applies panel data analysis to investigate the association between corporate governance and earnings management. I examine corporate governance along 2 dimensions: internal power balance and board monitor mechanisms. The results suggest that restricting CEO power does not help constrain earnings management, but introducing independent directors and NEDs can constrain both real earnings management as well as accrual manipulation. This paper not only contributes to the findings that high level corporate governance standards can constrain earnings management, but also comes up with new perspectives of corporate governance research.